Evaluative Meaning in Digital Discourse: A Corpus-Based Study of Xpose Uncensored YouTube Comments - Ruswan Dallyono; Annisa Vadia Haya (Universitas Islam Negeri Palopo, 2026)
People use social media comments to convey their opinions about different matters using their choice of words. The study analyzes user evaluation patterns in YouTube comments through collocational patterns, which researchers used to study the data. This study is based on a processed corpus of online comments totaling 118,662 tokens, collected from a YouTube video entitled Xpose Uncensored from the Trans7 channel, which covered the life of the pesantren school (Islamic Boarding School). The mixed-methods study was used by implementing collocation and concordance analysis to identify evaluative meanings that appear throughout comment discourse. The analysis results demonstrate that our evaluation consisted of three methods, namely action verbs that show support or demand and evaluative adjectives that show specific qualities, and imperative or condensed constructions, which create direct judgment presentations. Criticism and negative evaluation emerged as the most frequent explicitly evaluative category with 340 occurrences, exceeding appreciation and support, which accounted for 209 occurrences. In addition, communicative and metapragmatic responses were identified 561 times, suggesting that evaluation was often constructed through clarification, justification, and stance negotiation rather than through direct polarity alone in the comments on the representation of pesantren students and the pesantren school system.